Microbial lipid production by the yeast Lipomyces starkeyi InaCC Y604 grown on various carbon sources. Issue 1 (May 2021) - Juanssilfero, A B; Salsabila, P; Agustriana, E; Andriani, A; Fahrurrozi; Perwitasari, U; Sutrisno, A
Abstract: The use of non-renewable fuels in the transportation sector boosts the development of renewable biofuels, such as biodiesel. However, crops-based biodiesel production can cause the increment of deforestation and greenhouse gas emissions. This circumstance motivates the development of oleaginous microorganisms as alternative raw materials to overcome these problems. Lipomyces starkeyi is one of the potential oleaginous microorganisms due to its ability to produce higher lipid content. In addition, L. starkeyi is capable to grow in affordable carbon sources, such as lignocellulose and molases, which can reduce the production costs. The aim of this study is to determine the ability of L. starkeyi InaCC Y604 in producing lipids from various carbon sources and its effects on the composition of fatty acid methyl esters (FAME) and lipid contents. L. starkeyi InaCC Y604 were cultivated in nitrogen-limited mineral medium (-NMM) with various carbon sources, namely glucose, xylose, fructose, galactose, mannose, cellobiose and a mixture of glucose and xylose. The results showed that mixed glucose and xylose gave the best result with the lipid content achieved at 64.19% (w/w). The results obtained indicated that L. starkeyi InaCC Y604 could be a potential candidate for further optimizing biodiesel production.